PH-regulated hydrothermal synthesis and characterization of Sb4O5X2 (X = Br/Cl) and its use for the dye degradation of methyl orange both with and without light illumination. Issue 14 (15th March 2022) - Paul, Sayantani; Sen, Bibaswan; Chakraborty, Nirman; Das, Sangita; Mondal, Swastik; Chattopadhyay, Asoke P.; Ali, Sk Imran
Abstract : A pH-regulated hydrothermal synthesis method was employed to synthesize Sb4 O5 Br2 and Sb4 O5 Cl2 crystallites. Abstract : A pH-regulated hydrothermal synthesis method was employed to synthesize Sb4 O5 Br2 and Sb4 O5 Cl2 crystallites. Characterization is done by single crystal X-ray diffraction, powder X-ray diffraction, infra-red spectroscopy, scanning electron microscopy and DFT studies. The compounds crystallize in monoclinic symmetry with a P 21 / c space group. Complete structural analysis of the Sb4 O5 Br2 compound by using single crystal X-ray diffraction data is performed for the first time and a comparative study with Sb4 O5 Cl2 is also discussed. The SEM study reveals that the surface morphology changes with the variation of pH for bromide compounds, whereas pH change does not affect the morphology of the chloride analogues. Electronic band structures of the synthesized oxyhalides were investigated in order to understand their catalytic effects in the dye degradation reactions in dark as well as sunlight conditions.